2021
DOI: 10.1021/acs.langmuir.1c01070
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Nanogel Formation by Reactive Layer-by-Layer Assembly of Polyester and Branched Polyethylenimine via Aza-Michael Addition

Abstract: We here demonstrate the utilization of reactive layer-by-layer (rLBL) assembly to form a nanogel coating made of branched polyethylenimine (BPEI) and alkyne containing polyester (PE) on a gold surface. The rLBL is generated by the rapid aza-Michael addition reaction of the alkyne group of PE and the −NH2 groups of BPEI by yielding a homogeneous gel coating on the gold substrate. The thickness profile of the nanogel revealed that a 400 nm thick coating is formed by six multilayers of rLBL, and it exhibits 50 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…PEI is a hydrophilic macromolecule that contains primary, secondary, and tertiary amine groups, and its hyperbranched structure provides large polar contact areas, enabling interactions with other biomaterials. For instance, Yildirimkaraman et al 64 developed an electroactive nanogel coating using the LbL technique consisting of branched PEI and alkyne containing polyester on a gold surface. We hypothesized that the hyperbranched PEI structure would facilitate the formation of a 3D hydrogen-bonding network between the −NH 2 groups of the PEI compound and the phosphate group of the GMP, while preserving the integrity of the scaffold (Scheme 2).…”
Section: Guo/gmp-pei Hydrogel Preparation and Characterizationmentioning
confidence: 99%
“…PEI is a hydrophilic macromolecule that contains primary, secondary, and tertiary amine groups, and its hyperbranched structure provides large polar contact areas, enabling interactions with other biomaterials. For instance, Yildirimkaraman et al 64 developed an electroactive nanogel coating using the LbL technique consisting of branched PEI and alkyne containing polyester on a gold surface. We hypothesized that the hyperbranched PEI structure would facilitate the formation of a 3D hydrogen-bonding network between the −NH 2 groups of the PEI compound and the phosphate group of the GMP, while preserving the integrity of the scaffold (Scheme 2).…”
Section: Guo/gmp-pei Hydrogel Preparation and Characterizationmentioning
confidence: 99%
“…Recently, our group has been interested in the metal-free click reactions, modifications, and polymerization of electron-deficient triple bond-containing monomers such as acetylene dicarboxylic acid and its derivatives. We have shown that polyesters containing acetylene dicarboxylate on their backbone can be easily modified with aza-Michael and thiol-Michael reactions under benign conditions, in the absence of metal catalysts, and in high yields. We have demonstrated that diallyl esters of acetylene dicarboxylic acid can be functionalized similarly. , In light of the studies in the literature and foresights that we have gained with our studies on electron-deficient triple bond-containing monomers, we speculated that the activated triple bond-containing castor oil could be a versatile platform for the synthesis of bio-based functional materials and thermoset polymers. Here, we present the synthesis of propiolated castor oil and demonstrate its subsequent functionalization with a series of primary and secondary amines (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with gradient electrostatic LBL, the rLBL approach offers four major benefits, namely, (i) the covalent bond offers excellent stability, (ii) rLBL does not require additional cross-linking, (iii) rLBL may be used in aqueous or organic reaction types, and (iv) the latest deposited layer does not disassemble the previously deposited layer. , Using rLBL assembly with the aza-Michael reaction of branched polyethylenimine (BPEI) and polyester (PE) on the isocyanate-functionalized gold surface, our recent work showed that a 400 nm robust electroactive nanogel coating structure, allowing effective permeability mass and charge transfer, can be created. Results from X-ray photoelectron spectroscopy (XPS) depth profiling revealed that both polymers were present in each layer due to the presence of multiple functional groups in addition to the BPEI and PE intense layers of the nanogel . When interacting with surfaces, nanosized objects do not “feel” the presence of a gradient in the same way that larger objects do.…”
Section: Introductionmentioning
confidence: 99%